The Role of E-Performance in Improving Employee Performance Through Motivation - Regita Fitriana; Sih Darmi Astuti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the role of e-performance in improving employee performance through motivation at the Inspectorate of Central Java Province. This research is a type of quantitative research method with field observation and questionnaire. The population in this study is 141 employees. In determining the sample using the census sampling method. Out of a total of 141 employees, only 113 employees were used as respondents in this research. The data collection technique is carried out by distributing questionnaires that have been tested for validity and reliability, questionnaires distributed online through Google form and physical questionnaires distributed directly to respondents. The data analysis method used consisted of descriptive analysis, evaluation of the outer model, evaluation of the inner model, and evaluation of indirect effects (mediation). The data analysis tool in this study uses SmartPLS 3.0 software. The results of this study indicate that e-performance has a positive effect on employee performance, competence does not have a positive effect on employee performance, motivation has a positive effect on employee performance, e-performance has a positive effect on motivation, competence has a positive effect on motivation, e-performance has a positive effect on employee performance through motivation, and competence has a positive effect on employee performance through motivation.